Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
f-1(x) = +- sqrt(x + 6)
Step-by-step explanation:
f(x) = x^2 - 6
y = x^2 - 6
x = y^2 - 6
x + 6 = y^2
y = +- sqrt(x + 6)
f-1(x) = +- sqrt(x + 6)
Hi :)
Let's find the inverse of the function
——————————
Remember, inverse functions do the opposite things in the opposite order.
To find the inverse,
- replace [tex]\boldsymbol{f(x)}[/tex] with [tex]\boldsymbol{y}[/tex]
- swap x's and y's
- solve for y
Replace f(x) with y. (one step)
Then
[tex]\boldsymbol{y=x^2+6}[/tex]
Swap x's and y's (one step)
Then
[tex]\boldsymbol{x=y^2+6}[/tex]
Solve for y (several steps)
[tex]\boldsymbol{x-6=y^2}[/tex] > square root both sides
[tex]\boldsymbol{\sqrt{x-6}=y}[/tex] > swap y and √x-6
[tex]\boldsymbol{y=\sqrt{x-6}}[/tex]
[tex]\tt{Learn~More;Work~Harder}[/tex]
:)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.